On the altitude profile of lower ionospheric D-region response time delay during solar flares - Chakraborty, Sayak; Paul, Rakhi; Basak, Tamal (Frontiers in Environmental Science, 2022)
The D-region ionosphere is sluggish in nature while responding to the incoming solar radiation. We study the altitude (h) profile of mid-latitude D-region response time delay (Δt) during three chosen solar flares, namely, C5.2, M5.2, and X2.2 classes. We solve “electron continuity equation” numerically at each and every h to obtain Δt-h profile. We investigate the 1) latitudinal variation (over both Northern and Southern hemispheres) and 2) seasonal variation (throughout the year) of Δt-h profiles of each of these solar flares separately. We go over noteworthy variations of Δt-h profile for both 1) and 2) with reasonably different results over different hemispheres. Also, we study some contrasting behaviours of Δt-h profile of X2.2 class for both 1) and 2) in comparison to C5.2 or M5.2 classes. We conclude the outcome with possible explanations.